Characterisation of the cilia-associated Kinesin-16, KIF12 - Alghamdi, Hanan (2023)
Kinesin-16 is a family of kinesins that are only found in organisms that possess cilia or flagella. The human Kinesin-16, KIF12, is implicated as a polycystic kidney disease (PKD) modifier. Dysfunction of KIF12 may also be involved in the progression of certain types of diabetes and mutations to KIF12 have been shown to be strongly correlated with paediatric cholestatic liver disease.